2017
DOI: 10.1007/s10552-017-0977-9
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive risk factor associations with lobular and ductal carcinoma in the Carolina Breast Cancer Study

Abstract: Lobular tumors were associated with older age at first birth, increased lactation duration, and current oral contraceptive use. Etiologic heterogeneity by histology persisted after restricting to Luminal A subtype, suggesting both tumor histology and intrinsic subtype play integral parts in breast cancer risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 50 publications
1
9
1
Order By: Relevance
“…We found an increased risk of both IDC and ILC subtypes in women who were older at their first delivery, which is in agreement with the findings of some previous studies, but not all . Another study suggested that there is no significant difference between the risk of breast cancer subtypes and reproductive factors including the age of first delivery …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found an increased risk of both IDC and ILC subtypes in women who were older at their first delivery, which is in agreement with the findings of some previous studies, but not all . Another study suggested that there is no significant difference between the risk of breast cancer subtypes and reproductive factors including the age of first delivery …”
Section: Discussionsupporting
confidence: 92%
“…Ductal and lobular tumours are the two most frequently diagnosed subtypes of invasive breast carcinomas (75% and 15% of all malignant tumours, respectively), and these two subtypes have different clinical, molecular and pathologic features . However, only few epidemiological studies have examined the heterogeneity of the disease, and the differences in risk factors are not yet fully understood …”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer risk increases with later menopause [44]. Women who experience menopause at age 55 or older have about a 12% higher risk compared to those who do so between ages 50-54 [45,46]. In our study, we found no signi cant association between breast cancer risk and late menopauses.…”
Section: Discussioncontrasting
confidence: 70%
“…Studies of adult neoplasms including breast (1)(2)(3)(4)(5), colon (6)(7)(8), and prostate (9,10), have shown that subtyping, whether molecular or histologic, leads to identification of etiologic heterogeneity between tumor subtypes that may inform targeted public health prevention strategies. For example, in breast cancer, there are robust findings across multiple study populations showing evidence of etiologic heterogeneity by reproductive risk factors such as age at menarche, first birth, and menopause, as well as combined menopausal hormone therapy use for lobular, compared with ductal carcino-ma, and by molecular breast cancer subtype (1)(2)(3)(4)(5). Similarly, there is etiologic variation by histologic and molecular subtype for colorectal adenomas concerning combined hormone therapy use (6) and cigarette smoking (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%